Spesifikasi dan Identifikasi Hasil Tangkapan Garok Rajungan di Pelabuhan Perikanan Pantai (PPP) Bondet Kabupaten Cirebon, Jawa Barat - Dirja M.Si; Muhammad Danil Segi (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
Crayfish (Portunus pelagicus) is the leading export commodity of Indonesian fishermen. The increasing demand for exports and high selling prices have made fishermen at the Bondet Beach Fishing Port, Cirebon Regency, use garok crabs to maximize their catch. The purpose of this study was to identify tool specifications, catch yields, selectivity and productivity of garok crab fishing gear operated at the Bondet Coastal Fishery Port, Cirebon Regency, West Java. The research was carried out in April – June 2021. The method used was a case study method with quantitative descriptive analysis to determine the specifications of the tools and catches taken by interviewing fishermen. The results showed that the crab claws were included in the dredge gear category. Its components consist of body mouth, garok, frame, nets, and ropes of various sizes. The main catch of garok crab in Cirebon Regency consists of small crab (Portunus pelagicus), and by-catch in the form of shellfish, shrimp, cuttlefish, and demersal fish, with a total of 14 species. This tool is classified as non-selective because of the small size of the bag mesh construction (30 mm) so that this tool catches many species with large and small size fish caught. The average catch obtained from 5 trips was 23.8 kg, with the lowest catch on the 2nd trip, which was 19.7 kg and the highest on the 5th trip, which was 31.3 kg, while the average sweep area was 0.0040 km2 with an average productivity of 3.97 kg/hour and the highest catch rate value was obtained on the 5th trip, which was 5.21 kg/hour, while the lowest catch rate was found on the second trip, which was 3.28 kg/hour.